2018
DOI: 10.3844/ojbsci.2018.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dayak Onion (Eleutherine bulbosa (Mill.) Urb) on Uterine wall and Lipid Profiles of Ovariectomized Rat

Abstract: Menopause is a physiologic condition, in which women no longer experience menstruation. Decreased estrogen during and after menopause causes structural, physiological and biochemical changes that alter the health of women in general, both in organs and non-reproductive organs. Dayak onion contains eleuterinol, an naphtoqunone derivative that can be as SERM. Therefore, we evaluated the effects of dayak onions on lipid profiles and uterine wall. This study used female white rats of Sprague-Dawley. All groups, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Biological activities of the bulb extracts have been reported, including inhibit bacterial growth particularly Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa (Jiang et al, 2020). E. bulbosa bulb extracts could increase bone calcium level and bone weight (Bahtiar and Annisa, 2018), decrease the lipid profile of hypoestrogenic of rat, due to binding of eleutherinol to the estrogen receptors (Purnamasari and Bahtiar, 2018). The biological activities of E. bulbosa bulb extracts was correlated to its antioxidant content, including flavonoids and phenols (Preethy et al, 2016;Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Biological activities of the bulb extracts have been reported, including inhibit bacterial growth particularly Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa (Jiang et al, 2020). E. bulbosa bulb extracts could increase bone calcium level and bone weight (Bahtiar and Annisa, 2018), decrease the lipid profile of hypoestrogenic of rat, due to binding of eleutherinol to the estrogen receptors (Purnamasari and Bahtiar, 2018). The biological activities of E. bulbosa bulb extracts was correlated to its antioxidant content, including flavonoids and phenols (Preethy et al, 2016;Shi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The content in EEB associated with estrogen receptors is liquiritigenenin and liquiritigenin activity more to the β estrogen receptor, so it does not cause an increase in wet weight 31 . Other studies have shown that EEB does not cause an increase in wet uterus weight 32 . Daidzein which is a phytoestrogen compound in cowpeas will undergo biotransformation to equol.…”
Section: Pharmacokinetic Of Equol Analysismentioning
confidence: 85%
“…The positive control group using raloxifene did not show on the quality of life because it can cause vaginal dryness, pain, itching, and other such changes 35 , 36 . Estrogen therapy is known to be effective for treating vulvovaginal atrophy caused by hypoestrogenic conditions or due to increasing age in menopausal women 32 . The condition of decreasing estrogen levels in the blood causes a negative feedback mechanism that explains the occurrence of overexpression of REα 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in another study conducted by Bahtiar and Annisa [90], the bulb of E. bulbosa significantly increased the calcium level, weight, and bone length in hypoestrogenic rats compared to the tamoxifen-induced group. Other studies also indicated that the E.bulbosa bulb could reduce lipids in ovariectomized rats [91].…”
Section: Effect On the Reproductive System Disordersmentioning
confidence: 94%